Obstacles to development in Libya "Corruption as a model" (Sebha University Conference Proceedings, 2022)
Societies, especially in Libya, are rife with the phenomenon of corruption, which almost casts a shadow over all the joints, organs and sectors of the state. This is extremely dangerous for the development and growth of societies. Anti-corruption mechanisms have an important mark in eliminating all its manifestations and joints, as the phenomenon of corruption is an international phenomenon in terms of its effects. It takes an international nature, and is distributed to all countries of the world. Thus, its extension is horizontal and concentrated in varying proportions and degrees. Its extension is major and the local and international community felt the seriousness of this phenomenon.